Segmental sequencing of the upper body segments in unconstrained maximum overarm throws: An implication for coaching - Fu, A. C. L.; Cobley, S. P.; Sanders, R. H. (Scandinavian Journal of Medicine & Science in Sports, 2022)
Overarm throwing is an essential fundamental movement skill (FMS). Competency in throwing is critical to encourage physical activity throughout lifespan. However, the segmental sequencing characteristics of skilled throwing to achieve maximum ball release speed are unclear. Further, the standard instructions for segmental sequencing in coaching manuals are anecdotal and not based on scientific evidence. Therefore, the aim of this study was to establish the critical features of upper-body sequencing in skilled throwing for maximum speed. This would enable revised instructions for coaching throwing based on scientific evidence. The three-dimensional kinematics of 144 right-handed unconstrained maximum overarm throws were captured and analyzed. The quartiles of participants with the fastest and lowest ball release speed, normalized by height, were defined as the Skilled Group and Less Skilled Group, respectively. Paired t-tests were used to determine the differences in times of successive events within groups and independent t-tests for between-group differences in temporal space between events for all sequences. A characteristic segmental sequence of each group was defined as a sequence with significant within-group differences in two successive events (p < 0.001), while a critical segmental sequence was defined as a sequence with significant differences in temporal space both within groups and between groups (p < 0.001). The Skilled Group had six characteristic sequences, while two were found for the Less Skilled Group, summarized in the conceptual model. A single critical sequence of non-throwing arm elbow extension prior to shoulder extension was found. Five evidence-based instructions were recommended to add to the Australian FMS instruction manual.